Growth and characterisation of III-V semiconductor materials grown primarily by AME and PA-MBE - Goff, Lucy Elizabeth (2015)
This thesis describes the growth and characterisation of gallium nitride, indium nitride and indium gallium nitride semiconductors primarily carried out using a novel growth technique called Anion Modulation Epitaxy (AME) and also plasma-assisted MBE (PA-MBE). Characterisation was typically performed by x-ray diffraction, scanning electron microscopy and optical reflectance studies. All of the work in this thesis was carried out in the hope to improve layer structure and quality which in turn would create higher efficiency solar cells. Nanorods were grown using PA-MBE as these are known to form entirely defect-free material and this would be an attractive quality when trying to increase the efficiency. InN rods were grown at temperatures between 350 C and 450 C on SiC substrates of both Si- and C-polar faces at various indium fluxes to establish optimal growth conditions. It was found that a BEP flux of approximately 2x10-7 Torr and a growth temperature approximately 400 C provided a large array of rods. Samples produced tall, thin nanorods as well as short, fat ones. CBED analysis revealed that the tall nanorods were growing In-polar which mimics the behaviour seen for GaN. Photoluminscence (PL) data for the rods agrees with the bulk PL measurement of InN in the literature confirming that reasonable quality films have been produced. Coalescence of the rods was achieved by increasing the flux to 2x10-6 Torr. Also, p-n junctions were grown on both faces of SiC and preliminary tests have shown a response to light. A new growth method was developed from conventional PA-MBE known as Anion Modulation Epitaxy (AME) and gives rise to improved growth compared with equivalent samples by PA-MBE as the growth temperature is decreased. It also allows p-doping for GaN to be carried out at lower temperatures and more consistently. Direct comparison of GaN samples grown at equivalent temperatures by PA-MBE and AME show improved structural, electrical and optical properties for the samples grown using AME. It has also proven to be a useful tool for studying temperature changes at the substrate surface when using any pulsed growth technique. Substrate temperature was shown to vary by approximately 15 C each time the flow was interrupted. Slower, long-term trends were also monitored depending on the average nitrogen to metal ratio. An increase in overall temperature is derived from increasing metal rich growth, whereas the opposite effect is true for increased nitrogen rich growth. AME was also used for the growth of intermediate band solar cells (IBSC). The entire growth is easily monitored and altered using AME without altering the growth parameters drastically. Pulsing the nitrogen allows for variations in the metal cell fluxes to be kept under control at the surface. The discovery of `hidden' metal in the layer would have taken a lot longer to discover, and would have ruined the sample without utilising AME.